(untitled) (Journal of Engineering, 2011)
Mechanical degradation hampers the practical usage of polymers for turbulent drag reduction application. Mechanical degradation refers to the chemical process in which the activation energy of polymer chain scission is exceeded by mechanical action on the polymer chain, and bond rupture occurs. When a water-soluble polymer and surfactant are mixed in water solution, the specific structures (aggregates) are formed, in which polymer film is formed around micelle. In this work, Xanthan gum (XG) – Sodium lauryl ether sulfate (SELS) complex formation and its effect on percentage viscosity reduction (%VR) was studied. It was found that SELS surfactant reduced the mechanical degradation of XG much more efficiently than this polymer alone. Xanthan Gum (XG) has been tested for its shear stability and degradability. 0.5% and 1.0 % by weight concentration solutions were exposed to shear stirring at different speeds and time; also 0.5% through 1.5% by weight concentration solutions of SELS were added to XG solutions to determine the ability of SELS to reduce the mechanical degradation of XG. It has been noticed by measuring the percentage viscosity reduction (%VR) of the mixture of XG-SELS that the % VR decreases when added this surfactant to XG polymer